2013
DOI: 10.1007/s11999-012-2640-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Provider Selection for Elective Total Joint Arthroplasty

Abstract: BackgroundThe growth of consumer-directed health plans has sparked increased demand for information regarding the cost and quality of healthcare services, including total joint arthroplasty (TJA). However, the factors that influence patients' choice of provider when pursuing elective orthopaedic care, such as TJA, are poorly understood.Questions/purposes We evaluated the factors patients consider when selecting an orthopaedic surgeon and hospital for TJA. Methods Two hundred fifty-one patients who sought treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 15 publications
(20 reference statements)
6
55
0
Order By: Relevance
“…Although it is expected that this pattern of care (choosing an LVH when an HVH was closer) would have a negative effect on outcomes, this relationship has not been directly evaluated. The factors contributing to selection of a hospital and a surgeon are multifactorial [18,20] and may not be entirely under the patient's control. However, this evaluation of complication rates for patients who underwent surgery at an LVH instead of HVH within the same vicinity is needed to guide future decision making.…”
mentioning
confidence: 99%
“…Although it is expected that this pattern of care (choosing an LVH when an HVH was closer) would have a negative effect on outcomes, this relationship has not been directly evaluated. The factors contributing to selection of a hospital and a surgeon are multifactorial [18,20] and may not be entirely under the patient's control. However, this evaluation of complication rates for patients who underwent surgery at an LVH instead of HVH within the same vicinity is needed to guide future decision making.…”
mentioning
confidence: 99%
“…Furthermore, in a comparison of the educational levels and technical positions of physicians and physicians’ assistants between hospitals and community health centers, the constituent ratios for undergraduates and postgraduates (63.8%), and intermediate and senior positions (52.9%) in hospitals were higher relative to those observed in community health centers (33.2% and 39.8%, respectively) 31. Differences in medical resources and physicians’ technical skill levels led patients to seek treatment at large hospitals rather than smaller institutions 32,33. Therefore, dual practice in community health centers would increase the number of physicians with high education levels and senior technical positions in the community, which would increase the patients’ willingness to attend the centers, reduce the excessive influx of patients to large hospitals, and allow the provision of improved triage services for patients 34…”
Section: Discussionmentioning
confidence: 99%
“…Insurance status of provider and availability of appointments are highly influential factors in patients' choice of healthcare provider or physician (Abraham et al, 2011). Patients consider physicians' quality (measured as a combination of structural and outcome factors) is one of the most important factors in choosing a surgeon (Bozic et al, 2013) and, initially, an important factor in choosing a healthcare provider for a 'serious, but non-urgent health problem' (Fasalo et al, 2013). Patients consider expertise the most important factor in choosing a healthcare provider for Alzheimer's disease (Groenewoud et al, 2015).…”
Section: Structural Factorsmentioning
confidence: 99%
“…The standard of facilities is among the most influential in patients' healthcare provider choice for elective treatment (Laverty et al, 2013) Process factors. Existing research has demonstrated that patients consider the manner of physicians (e.g., spending adequate time answering questions, communicating clearly, valuing patients' opinion) (Bozic et al, 2013) as one of the most important factors in choosing a surgeon. Patients consider safety as one of the most important for choosing for choosing a healthcare provider for knee arthrosis, and continuity of care and relationship with the therapist for chronic depression (Groenewoud et al, 2015).…”
Section: Structural Factorsmentioning
confidence: 99%